Propensity Score Matched Analysis Comparing Robotic-Assisted with Laparoscopic Posterior Retroperitoneal Adrenalectomy. Issue 11 (1st November 2021) - Ma, Wenming; Mao, Yongxin; Dai, Jun; Alimu, Parehe; Zhuo, Ran; He, Wei; Zhao, Juping; Xu, Danfeng; Sun, Fukang
Abstract: Objectives: To compare the perioperative outcomes between robotic posterior retroperitoneal adrenalectomy (RPRA) with laparoscopic posterior retroperitoneal adrenalectomy (LPRA) for adrenal tumors and to identify which group of patients may benefit from RPRA. Methods: A total of 401 patients who fulfilled the inclusion criteria were collected and analyzed; among them, 86 and 315 patients underwent RPRA and LPRA, respectively. To adjust for potential baseline confounders, propensity score matching (PSM) was conducted at a 1:1 ratio. Patient demographics and perioperative outcomes were compared between the two groups. Results: After matching, no differences were found between the two groups in patient demographics or tumor characteristics. The median length of postoperative stay (3 vs. 4 days, p = 0.001) was significantly shorter in the RPRA group, but this group also showed a higher median total hospitalization cost (8121.89 vs. 4107.92 , p < 0.001). There was no difference in the median operative duration (100 vs. 110 min, p = 0.554), median estimated blood loss (50 vs. 50 ml, p = 0.730), transfusion rate ( p = 0.497) or incidence of postoperative complications ( p = 0.428). Conclusions: According to our research, RPRA leads to a shorter postoperative hospitalization stay but a higher total hospitalization cost than LPRA after propensity score matching.